2022
DOI: 10.1097/md.0000000000030511
|View full text |Cite
|
Sign up to set email alerts
|

A new marker predicting gestational diabetes mellitus: First trimester neutrophil/lymphocyte ratio

Abstract: Gestational diabetes mellitus (GDM) is a condition that is very common during pregnancy and has negative consequences for both mother and fetus. Insulin resistance has been shown as an important cause in the pathogenesis of GDM and lowlevel inflammation is suggested to be one of the underlying causes of insulin resistance. We aimed to investigate whether the neutrophil-lymphocyte ratio (NLR), which is an indicator of systemic inflammation, is a predictor for GDM. A total of 228 pregnant women, including 128 GD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…These data were in agreement with previous studies, showing an increased risk of developing GDM in the presence of a high BMI before pregnancy [ 36 , 37 ]. It is possible to hypothesize that the placenta responds to altered glucose metabolism already in the first trimester, secreting high HtrA1 levels, although GDM will only be diagnosed later in pregnancy when the altered maternal blood glucose levels become visible at the OGTT test.…”
Section: Discussionsupporting
confidence: 94%
“…These data were in agreement with previous studies, showing an increased risk of developing GDM in the presence of a high BMI before pregnancy [ 36 , 37 ]. It is possible to hypothesize that the placenta responds to altered glucose metabolism already in the first trimester, secreting high HtrA1 levels, although GDM will only be diagnosed later in pregnancy when the altered maternal blood glucose levels become visible at the OGTT test.…”
Section: Discussionsupporting
confidence: 94%
“…Most studies showed an increase in the above components in the GDM group compared with the NGT pregnancy. 21–23 The study by Sahin et al found that NLR was positively correlated with FPG (r = 0.285, p = 0.001) in GDM in the third trimester of pregnancy. 21 In contrast, the study of Hassan et al did not find any difference in the above components between pregnant women with GDM or without GDM.…”
Section: Discussionmentioning
confidence: 95%
“… 21–23 The study by Sahin et al found that NLR was positively correlated with FPG (r = 0.285, p = 0.001) in GDM in the third trimester of pregnancy. 21 In contrast, the study of Hassan et al did not find any difference in the above components between pregnant women with GDM or without GDM. 24 This difference is probably due to the difference in the timing of the study (the first or third trimester).…”
Section: Discussionmentioning
confidence: 95%
“…To predict the severity of SARS-CoV-2 virus infection, various methods have been used since the occurrence of the disease [7][8][9]. One of these methods was the closer surveillance of neutrophil-to-lymphocyte ratio (NLR) [10,11], which has already been evaluated in pregnant individuals battling with COVID-19 but also in other medical conditions (e.g., pre-eclampsia, gestational diabetes mellitus, and miscarriage) [12][13][14][15]. The neutrophil-tolymphocyte ratio is a simple and widely used biomarker, which is calculated by dividing the absolute neutrophil count (ANC) by the absolute lymphocyte count (ALC).…”
Section: Introductionmentioning
confidence: 99%